PENGARUH MANAJEMEN WAKTU MAHASISWA KERJA PART TIME TERHADAP PRESTASI AKADEMIK MAHASISWA JURUSAN PIPS FKIP UNIVERSITAS RIAU - Annisa Arisanti; Gusnardi Gusnardi; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to know the effect of time management of part timer students toward their academic achievements of PIPS students FKIP Universitas Riau. The data were obtained through survey on every class in PIPS FKIP. The survey told those 14 respondents of economic department, 9 respondents from civic department, and 10 respondents of history department. The results showed that time management gives positive and significant effects toward academic achievement partially and simultaneously, it clarify 25,7% while the rest 74,3% is probably due to other factors which are not involved in this research. It means that to improve students’ academic achievement can be done through improving students’ time management on or off campus.Key Words: Time Management, Part Time Student Work, Academic Achievement